Thiodiketopiperazines and Alkane Derivatives Produced by the Mangrove Sediment–Derived Fungus Penicillium ludwigii SCSIO 41408 - Cai, Jian; Wang, Xueni; Yang, Zaizhun; Tan, Yanhui; Peng, Bo; Liu, Yonghong; Zhou, Xuefeng (Frontiers in Microbiology, 2022)
A new trithiodiketopiperazine derivative, adametizine C (1), and five new alkane derivatives (7–11), were isolated from the mangrove sediment–derived fungus Penicillium ludwigii SCSIO 41408, together with five known dithiodiketopiperazine derivatives (2–6). Their structures were elucidated on the basis of spectroscopic analysis, and the absolute configuration of 1 was determined by X-ray crystallographic analysis. In a variety of bioactivity screening, 1–5 exhibited some selective antifungal or antibacterial activities. Compounds 1–3 showed cytotoxicity against prostate cancer cell line 22Rv1 with half maximal inhibitory concentration (IC50) values of 13.0–13.9 μM; moreover, 3 showed obvious activity against another prostate cancer PC-3 cells with an IC50 value of 5.1 μM. Further experiments revealed that 3 could significantly reduce PC-3 cells colony formation and induce apoptosis in a dose-dependent manner. Several compounds also exhibited obvious inhibitory activities of lipopolysaccharide–induced nuclear factor-κB with IC50 values range from 8.2 to 21.5 μM, and 1, 5, and 9 were further evaluated for their effects on receptor activator of NF-κB ligand (RANKL)-induced osteoclastogenesis. Adametizine C (1), with the strongest inhibitory activity against RANKL-induced osteoclast differentiation in bone marrow macrophage cells with 10 μM, was suggested to be the promising lead compound for the treatment of osteoclast-related diseases.